2022
DOI: 10.3390/membranes12100988
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Valuable Aromas from Sardine Cooking Wastewaters by Pervaporation with Fractionated Condensation: Matrix Effect and Model Validation

Abstract: Due to the lack of studies addressing the influence of real food matrices on integrated organophilic pervaporation/fractionated condensation processes, the present work analyses the impact of the real matrix of sardine cooking wastewaters on the fractionation of aromas. In a previous study, a thermodynamic/material balance model was developed to describe the integrated pervaporation—a fractionated condensation process of aroma recovery from model solutions that emulate seafood industry aqueous effluents, aimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Several studies have shown strong antioxidant activity mainly due to its high total phenolic content. As previously mentioned, the acorn shell extract showed potential in the stabilization of aromas [ 9 , 22 ] and of the bioactive fraction (mainly composed of proteins and lipids) of SCW [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown strong antioxidant activity mainly due to its high total phenolic content. As previously mentioned, the acorn shell extract showed potential in the stabilization of aromas [ 9 , 22 ] and of the bioactive fraction (mainly composed of proteins and lipids) of SCW [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…A water extraction method was chosen to obtain the acorn shell extract in this study based on the methodologies reported in the literature [ 9 , 18 , 22 , 23 , 24 , 25 ]. Some authors demonstrated that water-soluble phenolics may impact antioxidant potential more than methanol-soluble ones [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations